Cumulative pregnancy and live birth rates through assisted reproduction in women 44–45 years of age: is there any hope? - Raz, Nili (J Assist Reprod Genet, 2017)
PURPOSE: The purpose of the study is to calculate the cumulative pregnancy rate and cumulative live birth rate in women undergoing in vitro fertilization (IVF) at ages 44–45. METHODS: The study calculated cumulative live pregnancy rate and cumulative live birth rate of 124 women aged 44 to 45 years old who commenced IVF treatment. MAIN OUTCOME MEASURES: The main outcome measures are cumulative live pregnancy rate and cumulative live birth rate. RESULTS: Cumulative live pregnancy rates following 1, 2, 3, and 4 cycles were 5.6, 11, 17, and 20%, respectively, with no additional pregnancies in further cycles. Cumulative live birth rates following 1, 2, and 3 cycles were 1.6, 3, and 7%, respectively, with no additional live births in further cycles. CONCLUSIONS: The cumulative pregnancy rate rises during the first 4 cycles and cumulative live birth rate rises during the first 3 cycles, with no additional rise in pregnancies or deliveries thereafter, suggesting that it is futile to offer more than 3 cycles of treatment to 44–45-year-old women.